Description of nymphs and additional information on Nabis ashworthi (Hemiptera: Heteroptera: Nabidae) from Patagonia, Argentina - Cornelis, Marcela Fabiola (2016)
Immature stages III-V are described for the first time and additionalinformation on the males and females of Nabis ashworthi Faúndez & Carvajal,2014 (Hemiptera: Heteroptera: Nabidae: Nabinae) are given, including descriptions of their genitalia, based on specimens from the Argentine Patagonia. This is the fi rst record of this species from Argentina. The geographical distribution and habitat of Nabis ashworthi are discussed.